Ocorrência de nematoides em viveiros de produção de mudas de seringueira no estado de São Paulo - Paes-Takahashi, Vanessa Dos Santos [UNESP]; Soares, Pedro Luiz Martins [UNESP]; De Brito, Paulo Fernando; Carneiro, Franciele Alves [UNESP]; Dos Santos, Jaime Maia [UNESP] (My University, 2016)
Heveiculture plays an important role in São Paulo State, which contains more than half of the Brazilian natural rubber production. Nematodes are important pathogens that can cause significant losses to many crops, including rubber trees. The aim of this work was to survey nematode occurrence in rubber tree nurseries in São Paulo State. Agricultural Defense Coordination of São Paulo (CDA)/Office of Agricultural Defense Barretos (EDA) staff collaborated on the survey. Sixty nurseries were sampled from the main seedling production center of the state. The nematodes with the highest frequency and density were Meloidogyne and Pratylenchus. The main species found were M. incognita, M. exigua, P. brachyurus, and Rotylenchulus reniformis. Pratylenchus brachyurus was the most frequent species found on the roots of rubber tree seedlings, and is considered a key nematode to the crop. This work represents the first report of M. exigua causing damage to rubber tree seedlings in São Paulo State.
Nematode occurrence in rubber tree nurseries in São Paulo State
Keywords: Hevea brasiliensis; Meloidogyne exigua; Nurseries; Pratylenchus brachyurus